Optimum coil insertion speed of various coils in brain aneurysm embolization in vitro. Issue 5 (October 2016) - Konishi, Yoshifumi; Takeuchi, Masataka; Fukasaku, Kazuaki
A coil must comprise material with shape memory to perform optimal coil embolization. To achieve this, the alloy characteristics of the coil (hardness, shape, and thickness) must be understood. In this experiment, a catheter was fixed in the bright position and the movement of the coil was observed under a constant rate of insertion; the optimal insertion rate during clinical use was investigated. The first coil insertion speed was evaluated using simulated aneurysms in an in vivo arterial model. The results showed that the insertion force relates to the deployment shape of the coil, that the feedback through the force indicator using sound is very effective, and that the recorder is useful for analysis of coil embolization. The inserted coils during aneurysm embolization were able to wind uniformly within the aneurysm due to a variety of factors (guiding or micro-catheter position and kick-back phenomenon such as delivery wire). Optimal speed is achieved with proper coil design, which allows the coil to be inserted into the aneurysm. The shape and size of the aneurysm can help determine the necessary size and design of the coil that should be used during the optimal speed range. Aneurysm wall and coil characteristics are considered, along with the friction state of the coil (hardness, shape, and thickness), leading to improvements in safety during the insertion procedure at optimum speed.